Insomnia, Health-Related Quality of Life and Health Outcomes in Children: A Seven Year Longitudinal Cohort - Combs, Daniel (Sci Rep, 2016)
Insomnia is common in children, and is associated with decreased school performance and increased psychopathology. Although adult insomnia is linked to worsened health-related quality of life (HRQOL), there is insufficient data evaluating insomnia and HRQOL in children. We examined the HRQOL and health associations of insomnia in a longitudinal cohort of 194 children (96 girls, age at study start 8.7 ± 1.6 years, age at data analysis 15.0 ± 1.8 years) over 7 years. International Classification of Sleep Disorders, second edition (ICSD2) derived insomnia was seen intermittently in 27% of children, and was persistent in 4%. Children reporting ICSD2-derived insomnia had lower HRQOL. Additionally, the presence of insomnia was associated with an increased risk of reporting a new medical condition (intermittent insomnia odds ratio 5.9 [95% CI 1.3–26.7, p = 0.04], persistent insomnia odds ratio 8 [95% CI 2.3–27.7, p = 0.001]). Persistent ICSD2-derived insomnia was associated with an increased risk of reporting a new medication (odds ratio 4.9 (95% CI 1.0–23.6), p = 0.049), and reporting a new psychiatric medication (odds ratio 13.7, 95% CI: 2.6–73.5, p = 0.002). These associations were present even after adjusting for socioeconomic factors and the presence of obstructive sleep apnea. Insomnia in children is associated with worsened HRQOL and health outcomes.